2021
DOI: 10.3390/medicines8110064
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of the Serological Markers of Transfusion-Transmissible Infections among Volunteer Blood Donors of Kosti Obstetrics and Gynecology Hospital

Abstract: Background: Transfusion-transmissible infections are well-known global health challenges. The present study is proposed to investigate the seropositivity of anti-HIV1/2, anti-HCV, HBsAg, and anti-T.pallidum among volunteer blood donors of Kosti Obstetrics and Gynecology Hospital. Methods: Our study was conducted in a cross-sectional retrospective manner. The data of donors who attended Kosti Obstetrics and Gynecology Hospital throughout 2016 to 2018 were reviewed and retrieved manually from blood bank records.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
(158 reference statements)
0
1
1
Order By: Relevance
“…The prevalence was higher for HCV (2.90%) followed by HBV (1.60%), HIV (1.30%) for closing with Syphilis (0.2%). Our finding was lower when compared to study done by Yacob et al (20), Alex et al 21 , Babiker et al 22 who found 12.9 %,10.1 % and 22.52 %, successively. The reason for the lower rate of prevalence of TTI in this study compared with other studies may be due to the efficacy of the screening technique used before blood taking and also may be because of existence of different magnitude of risk factor for contracting transfusion transmitted infection.…”
Section: Prevalence Of Transfusion Transmitted Infectionscontrasting
confidence: 80%
“…The prevalence was higher for HCV (2.90%) followed by HBV (1.60%), HIV (1.30%) for closing with Syphilis (0.2%). Our finding was lower when compared to study done by Yacob et al (20), Alex et al 21 , Babiker et al 22 who found 12.9 %,10.1 % and 22.52 %, successively. The reason for the lower rate of prevalence of TTI in this study compared with other studies may be due to the efficacy of the screening technique used before blood taking and also may be because of existence of different magnitude of risk factor for contracting transfusion transmitted infection.…”
Section: Prevalence Of Transfusion Transmitted Infectionscontrasting
confidence: 80%
“…Also, the present rate is less than that has been stated in other previous studies in Basra province (0.2%) 7. In addition, the prevalence of HBsAg in blood donors in Basra is less than what has been reported from other countries in the region including Qatar, Jordan, Sudan, Egypt, Saudi Arabia, Lebanon, Iran and Pakistan 11 21–26…”
Section: Discussioncontrasting
confidence: 68%
“…These rates were higher in women than male, but this needs to be confirmed. Yet, these rates are less than what was found in other parts of Iraq including Karbala governate (0.76%), Anbar province in the west of Iraq (1.09%), in the Arab world and foreign countries including Qatar (0.45), Saudi Arabia (0.53), Sudan (6.6%), Pakistan (3.1%) and China (0.88%) 11 20 22 31–34…”
Section: Discussionmentioning
confidence: 80%
“…Sexually transmitted infections are currently a major public health problem. In addition, many of these infections are transmissible through blood transfusions, such as HIV, hepatitis B and C, syphilis, HTLV and Chagas disease (1,2,7,8,9,11) .…”
Section: Discussionmentioning
confidence: 99%
“…Sexually transmitted infections (STIs) are currently a serious public health problem, impacting the health of the entire population in the world (1) . Many infections are transmissible through blood transfusions, also becoming widely known and publicized global health challenges (2) .…”
Section: Introductionmentioning
confidence: 99%